Removal of reduction of free fatty acid in sludge palm oil via acid catalyzed reaction for biodiesel production - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Mohd. Hakimi, Noor Irma Nazashida; Mohd. Siran, Yosri; Tahiruddin, Shawaluddin (2010)
In this study sulphuric acid has been used in pre-treatment of sludge palm oil for biodiesel production by esterification process. The purpose of pre-treatment process was reducing the free fatty acids (FFA) content in the sludge palm oil (SPO) to a minimum level for biodiesel production. Esterification process of SPO was carried out to evaluate suphric acid as acid catalyst in dosage range (0.25-2.75% wt/wt), molar ratio of methanol to SPO (6:1-14:1), temperature (40-80o C), reaction time (30-120 min) and stirrer speed (200-800 rpm). The results showed that the FFA of SPO reduced from 23% to less than 2% FFA using 0.25% wt/wt of sulphuric acid, the molar ratio of methanol to oil was 8:1 at 60 minutes reaction time and 60 oC.